Finite element analysis of automotive intake manifold using CAE software - Muhammad Haikal, Haron (2008)
This project focused on simulation testing of automotive intake manifold design using Computer Aided Engineering software. Finite element Random Vibration analysis is conducted on Proton WAJA 1.6 intake manifolds designs for material cast aluminium alloy AlSi12 and glass-fibred polyamide PA6 GF30. The purpose of this project is to study the computational maximum stress on the model due to the effect of engine vibrations and pressure pulsation loads. The input data of vibrations and pressure pulsation loads are taken from previous studies. The softwares used are SOLIDWORK 2005 and ALGOR V16. Base on the simulation results obtained, the maximum stress of both materials are compared to distinguish which is better in resisting the vibration loads applied.